If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 63x + 25x = 300 + 25x Combine like terms: 63x + 25x = 88x 88x = 300 + 25x Solving 88x = 300 + 25x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-25x' to each side of the equation. 88x + -25x = 300 + 25x + -25x Combine like terms: 88x + -25x = 63x 63x = 300 + 25x + -25x Combine like terms: 25x + -25x = 0 63x = 300 + 0 63x = 300 Divide each side by '63'. x = 4.761904762 Simplifying x = 4.761904762
| 5-b=29 | | -6x+2x-9x= | | y+5y=3y | | 6x-10=2(2x+1) | | 23-13=5(x-1) | | 2x(2x)-224=0 | | -5(2y-10)-y=-4(y-5) | | 0.13y+0.05(y+5000)=1690 | | 6x-8x+2=x-3+5 | | -2(w+3)-w-5=-3(w+5)+4 | | x+24+4x=-26-4x-31 | | -5(w+2)-w-7=-6(w+4)+7 | | 3x-1=4x+1 | | -29p-6(5-6p)=3(p-4)-34 | | .5x(x)-242=0 | | 5z^2-7z=-3z-7 | | 4.9t^2+15t+1.9=0 | | (x+1.8)-(0.1x+7)=9 | | 1-5x-y=0fory | | -3(2-4n)=10 | | 0.34=logx | | (x+26)-(0.1x+8)=10 | | 7(5(x-1))+3=17 | | (x+2.7)-(0.7x+4)=12 | | -4x+6x-7=2(x-3)-4 | | 5+10x=4+10x | | 9x-5=2(4x+3)-1 | | -6(y+9)=-5y-5 | | 15z^4-13z^2+2=0 | | -7(z-3)=-6z-9 | | x-44=9 | | 9(x+4)-3x=3(2x+2)-7 |